Photosynthetic performance and nutrient uptake under salt stress: Differential responses of wheat plants to contrasting phosphorus forms and rates - Loudari, Aicha; Mayane, Asmae; Zeroual, Youssef; Colinet, Gilles; Oukarroum, Abdallah (Frontiers in Plant Science, 2022)
Salt stress impacts phosphorus (P) bioavailability, mobility, and its uptake by plants. Since P is involved in many key processes in plants, salinity and P deficiency could significantly cause serious damage to photosynthesis, the most essential physiological process for the growth and development of all green plants. Different approaches have been proposed and adopted to minimize the harmful effects of their combined effect. Optimising phosphorus nutrition seems to bring positive results to improve photosynthetic efficiency and nutrient uptake. The present work posed the question if soluble fertilizers allow wheat plants to counter the adverse effect of salt stress. A pot experiment was performed using a Moroccan cultivar of durum wheat: Karim. This study focused on different growth and physiological responses of wheat plants grown under the combined effect of salinity and P-availability. Two Orthophosphates (Ortho-A & Ortho-B) and one polyphosphate (Poly-B) were applied at different P levels (0, 30 & 45 ppm). Plant growth was analysed on some physiological parameters (stomatal conductance (SC), chlorophyll content index (CCI), chlorophyll a fluorescence, shoot and root biomass, and mineral uptake). Fertilized wheat plants showed a significant increase in photosynthetic performance and nutrient uptake. Compared to salt-stressed and unfertilized plants (C+), CCI increased by 93%, 81% and 71% at 30 ppm of P in plants fertilized by Poly-B, Ortho-B and Ortho-A, respectively. The highest significant SC was obtained at 45 ppm using Ortho-B fertilizer with an increase of 232% followed by 217% and 157% for both Poly-B and Ortho-A, respectively. The Photosynthetic performance index (PItot) was also increased by 128.5%, 90.2% and 38.8% for Ortho-B, Ortho-A and Poly B, respectively. In addition, Poly-B showed a significant enhancement in roots and shoots biomass (49.4% and 156.8%, respectively) compared to C+. Fertilized and salt-stressed plants absorbed more phosphorus. The P content significantly increased mainly at 45 ppm of P. Positive correlations were found between P-uptake, biomass, and photosynthetic yield. The increased photochemical activity could be due to a significant enhancement in light energy absorbed by the enhanced Chl antenna. The positive effect of adequate P fertilization under salt stress was therefore evident in durum wheat plants.